Estimating heritability of song considering within-individual variance in a wild songbird: The collared flycatcher - Jablonszky, Mónika; Canal, David; Hegyi, Gergely; Herényi, Márton; Laczi, Miklós; Lao, Oscar; Markó, Gábor; Nagy, Gergely; Rosivall, Balázs; Szász, Eszter; Török, János; Zsebõk, Sándor; et al. (Frontiers in Ecology and Evolution, 2022)
Heritable genetic variation is a prerequisite for adaptive evolution; however, our knowledge about the heritability of plastic traits, such as behaviors, is scarce, especially in wild populations. In this study, we investigated the heritability of song traits in the collared flycatcher (Ficedula albicollis), a small oscine passerine with complex songs involved in sexual selection. We recorded the songs of 81 males in a natural population and obtained various measures describing the frequency, temporal organization and complexity of each song. As we had multiple songs from each individual, we were able to statistically account for the first time for the effect of within-individual variance on the heritability of song. Heritability was calculated from the variance estimates of animal models relying on a genetic similarity matrix based on Single Nucleotide Polymorphism screening. Overall, we found small additive genetic variance and heritability values in all song traits, highlighting the role of environmental factors in shaping bird song.